AN ALTERNATE METHOD TO DETERMINE DENSITY OF SOLIDS ACCORDING TO ARCHIMEDES’ PRINCIPLE - Waseem, Shabana (The Nucleus, 2011)
To measure density of a solid object, according to Archimedes’ principle, hanging pan balance or toploading balance with density measurement kit are used. In the conventional method, weight of water displaced is calculated in terms of weight of the object hanged in water. We report a new and easier method to determine the density of a solid object based on same principle by using a toploading balance, but without any density measurement kit. In the new approach, weight of water displaced is measured directly on the balance. The proposed method is simpler, quicker and accurate.